The Image of Alexander in the Artistic Interpretation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The image of Alexander in the artistic interpretation. The article is devoted to the analysis of Alexander's image in the artistic interpretation in the works of Navoi.